1992
DOI: 10.1063/1.463666
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative (nonpairwise) effects in water trimers: An ab initio molecular orbital study

Abstract: Articles you may be interested inThe Jahn-Teller effect and spin-orbit coupling in alkali trimers: Spectroscopic experiments and ab initio calculations AIP Conf. Proc. 1504, 483 (2012); 10.1063/1.4771745An ab initio molecular orbital study of the nuclear volume effects in uranium isotope fractionations Hydrogen bonding and cooperative effects in mixed dimers and trimers of methanol and trifluoromethanol: An ab initio study Ab initio theoretical study of dipole-bound anions of molecular complexes. Water trimer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
121
0
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(136 citation statements)
references
References 53 publications
12
121
0
3
Order By: Relevance
“…1(b), where one hardly finds any absorption features except for the trimer peaks in the bonded-OH region, the cluster responsible for the ν s tail and ν as shoulder should not be different from the trimer. While the most stable isomer of the trimer, denoted by cyclic (da, da, da), 35 has the three molecules playing both the roles of the proton-donor and -acceptor without satisfying the condition described above, metastable isomers such as chain (a, d 2 , a) and cyclic (a 2 , d 2 , da) do. 35 However, gaussian fitting has revealed that the integrated intensities of the two trimer peaks at 3497 and 3528 cm −1 in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1(b), where one hardly finds any absorption features except for the trimer peaks in the bonded-OH region, the cluster responsible for the ν s tail and ν as shoulder should not be different from the trimer. While the most stable isomer of the trimer, denoted by cyclic (da, da, da), 35 has the three molecules playing both the roles of the proton-donor and -acceptor without satisfying the condition described above, metastable isomers such as chain (a, d 2 , a) and cyclic (a 2 , d 2 , da) do. 35 However, gaussian fitting has revealed that the integrated intensities of the two trimer peaks at 3497 and 3528 cm −1 in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While the most stable isomer of the trimer, denoted by cyclic (da, da, da), 35 has the three molecules playing both the roles of the proton-donor and -acceptor without satisfying the condition described above, metastable isomers such as chain (a, d 2 , a) and cyclic (a 2 , d 2 , da) do. 35 However, gaussian fitting has revealed that the integrated intensities of the two trimer peaks at 3497 and 3528 cm −1 in Fig. 2(a) are increased by 23% and 47% after annealing, respectively, in contrast to the 37 % intensity reduction of the 3710 cm −1 shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a very good correlation exists between the charge density at the HB critical point and the strength of the interaction. 8,12,13,23 For this purpose the charge densities at the bond critical points for all systems were located at the HF/6-311ϩϩG(d, p) level of theory. 40 Total interaction energies for the various clusters are calculated as…”
Section: Computational Detailsmentioning
confidence: 99%
“…5 Theoretical calculations have been supportive of this picture. [6][7][8][9][10][11][12][13][14][15][16] Of particular interest are the recent studies of the structural and energetic properties of hydrogen-bonded water, 7,8 methanol, [9][10][11][12][13][14] and water-methanol complexes. 15,16 It has been found that the dimers have linear hydrogen-bonded structures, while the results for higher oligomers are consistent with cyclic structures.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for instance, the water trimer shows a basicity comparable to that of ammonia. [1][2][3] A number of theoretical studies have been devoted to analyze the cooperativity effects in hydrogen bonded systems. 4 One of the most recent incorporations to the field of HBs corresponds to those cases where the HB acceptor is a negatively charged hydrogen.…”
Section: Introductionmentioning
confidence: 99%